The impact of a readiness program for implementing and sustaining continuous improvement processes. Issue 6 (10th October 2016) - Jaca, Carmen; Paipa-Galeano, Luis; Viles, Elisabeth; Mateo, Ricardo
Abstract : Purpose: The purpose of this paper is to describe a readiness programme designed to increase employees' awareness of order and cleanliness as a way of building the necessary foundation for implementing and sustaining continuous improvement processes. In this paper, the authors propose a new readiness programme based on the principles of 5S, with the aim of strengthening employees' motivation and involvement prior to 5S being implemented. Design/methodology/approach: The research is based on case study methodology, followed by a programme of four structured activities. The validity of the programme is shown through the implementation of the activities in two different organizations. Findings: The readiness programme was applied before 5S was successfully implemented. The degree of awareness and motivation of the programme participants improved as a result of these activities. Moreover, the activities increased people's motivation to participate in improvement activities. Originality/value: Applying a readiness programme before implementing 5S can help organizations to achieve and sustain improvement activities, thus increasing worker commitment and motivation.